Developments of Rice Cell Suspension Culture and A Novel Strategy for Screening New Resistant Lines to Rice Blight Disease Caused by Xanthomonas oryzae pv. oryzae - Restu Rizkyta Kusuma; Liliek Sulistyowati; Chiu-Chsiung Cheng; Yi-Hsien Lin (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
The research aimed to develop a rice cell culture system with high proliferation and screening resistant cell lines of rice to bacterial blight disease caused by Xanthomonas oryza pv. oryzae (Xoo). The culture cells obtained from the callus, cultured on CS-1 medium containing 3 % sucrose and 2 mg L-1 2,4-D for 4 weeks. The results showed that proliferation cell was signifcantly increased 1-fold in 3 weeks of primary culture in CS-1 conditioned medium (fresh/spent medium ratio 1:1) containing 3 % sucrose, 0.5 % glucose, 0.05 % fructose and 2 mg L-1 2,4-D. This medium was used to screen the cell lines through applying culture filtrate of Xoo. The method was to find a novel cell line which could produce high amounts of reactive oxygen species (ROS). Screening results showed 33 % cell lines were strong ROS-producing, two cell lines were selected and cultured for second round screening. The ratio of strong ROS-producing cell lines was increased up to 67 % in the third round screening. The strong ROS-producing cell lines in third round screening can be further cultured for plant regeneration. The rice cell lines with high ROS production may have potential of resistant cell lines against Xoo.